(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: To document the potential relationship between Helicobacter pylori infection (H. pylori), ABO and Rhesus (Rh) blood groups in affected individuals with peptic ulcer disorder. MATERIALS AND METHODS: This cross-sectional, research was accomplished from February 2021 to May 2021 among individuals experiencing dyspeptic conditions visiting Endoscopy Unit of Janakpur Provincial Hospital. All the patients were investigated for their blood group phenotype and Rhesus dependent through slide hemagglutination test. Also all the patients went through esophagogastroduodenoscopy (EGD) in order to identify peptic ulcer disease. Gastric biopsies were acquired and evaluated for H. pylori through urease test. RESULTS: A total of 103 patients were registered in this study, which included 49 males and 54 females with a mean age of 15-77 years. H. pylori was found positive in 75(72.8%) cases and negative in 28 (27.2%) cases, Blood group A, B, AB and O were found in 19.4%, 33.0%, 13.6%, and 34.0% of the patients respectively. Relatively higher prevalence of H. pylori was found in each blood groups O (33.3%) and B (33.3%) compared to blood group A (20.1%) and AB (13.3%). However, association of ABO blood group and prevalence of H. pylori was found to be insignificant (p=0.991). CONCLUSIONS: The study concluded that B blood group people were more prone to H. pylori infection. Our study revealed that H. pylori contamination was definitely an endemic issue, which needs to be handled by enhancing hygiene, supply of filtered water and in addition other measures for its elimination. Further meticulous studies are needed to establish relationship between blood type and H. pylori contamination in different age groups.